Stabilizing oxygen vacancies and promoting electrostrain in lead-free potassium niobate-based piezoelectrics over wide temperature ranges - Bingcheng Luo; Wei Feng; Suwei Dai; Hongzhou Song; Yunyi Wu; Jie Zhang (Journal of Advanced Ceramics, 2024)
Piezoelectric ceramics provide high strain and large driving forces in actuators. A large electrostrain can be realized by the introduction of point defects such as vacancies, interstitial defects, and substitution defects. With Mn doping, a significant increase in the reversible electrostrain from 0.05% to 0.17% could be achieved in potassium niobite lead-free piezoelectric ceramics. The origins of the large electrostrain were analyzed via in situ X-ray diffraction (XRD) under an electric field. The electrostrain and other typical electrical properties of the samples were measured at various temperatures, which enabled the ceramics to perform under a very wide temperature range, such as −80–130 °C for the 0.5 mol% Mn-doped sample with low dielectric loss (≤ 0.02). More importantly, combined with characterizations of the defect behavior by thermally stimulated depolarization current (TSDC), the failure mechanisms of electrostrain in a high-temperature environment could be revealed, which was associated with synergistic damage to the defects caused by the electric field and high temperature. The results can provide good ideas and a basis for the design of piezoelectric materials with good electrostrain stability over a wide temperature range.